2017
DOI: 10.1038/s41598-017-03249-z
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics reveals the therapeutic effect of HuangQi Injections in cisplatin-induced nephrotoxic rats

Abstract: The side effects of cisplatin (CDDP), notably nephrotoxicity, greatly limited its use in clinical chemotherapy. HuangQi Injections (HI), a commonly used preparation of the well-known Chinese herbal medicine Astragali radix, appeared to be promising treatment for nephrotoxicity without compromising the anti-tumor activity of CDDP. In this study, the urinary metabolomics approach using liquid chromatography time of flight mass spectrometry (LC-TOF/MS) was developed to assess the toxicity-attenuation effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…It was found that some metabolic pathways were shared by some models, such as the citrate cycle, and taurine and hypotaurine metabolism. The same results had been previously reported in experimental models of aristocholic acid and cisplatin (Li et al, 2017; Zhang et al, 2016; Zhao et al, 2015). Simultaneously, glycine, serine and threonine metabolism, together with arginine and proline metabolism, had been reported in adenine and cisplatin model, respectively, (Li et al, 2017; Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…It was found that some metabolic pathways were shared by some models, such as the citrate cycle, and taurine and hypotaurine metabolism. The same results had been previously reported in experimental models of aristocholic acid and cisplatin (Li et al, 2017; Zhang et al, 2016; Zhao et al, 2015). Simultaneously, glycine, serine and threonine metabolism, together with arginine and proline metabolism, had been reported in adenine and cisplatin model, respectively, (Li et al, 2017; Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…NMR-based metabolomics is a powerful tool for systematic investigation of potential biomarkers in biofluids 24 . Urine, a waste and filtrate from kidney, is non-invasive and directly reflects renal status 21 , 36 . Therefore, urinary metabolomics coupled with multivariate analysis provide a powerful approach to investigate metformin’s effect on Pb-induced renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Non-targeted and targeted strategies are commonly used for metabolomics analyses. The former are suitable for discovering unknown biomarkers, and the latter are used to quantify well-known targets 21 , 22 . One human serum metabolomics study showed that co-exposure to heavy metals disturbs lipid and amino acid metabolism 23 .…”
Section: Introductionmentioning
confidence: 99%
“…RA membranaceus is widely used in clinical treatment of digestive system, respiratory system, cardiovascular diseases, endocrine diseases, and metabolic diseases. It has an enhancing effect on regulating energy metabolism and immune and metabolic functions [ 35 ]. RA also showed advantages including significant treatment effect, no toxic side effects, and less adverse reactions [ 36 – 40 ].…”
Section: Discussionmentioning
confidence: 99%